Target 2015: Education for All (EFA) action plan - Trinidad and Tobago. Ministry of Education (Ministry of Education, 2006)
UNESCO’s Education for All (EFA) is the particular focus of this plan, which acknowledges global educational goals, first at basic levels, then incorporating regional standards. Therefore, in moving to define national goals, objectives, and strategies, this national plan of Trinidad and Tobago’s Ministry of Education takes into account the prominence of CARICOM and the CARICOM Single Market Economy (CSME), and the need for certification that equips citizens to move freely and be accepted as competent in their chosen work. It covers eight action areas: 1) Early childhood care and education; 2) Primary education; 3) Education of Youth and adults; including at the secondary level 4) Enabling teachers; 5) Involvement of civil society; 6) The use of information and communication technology (ICT); 7) Performance accountability, national investments and resource mobilization; and 8) Safe schools and the healthy citizen.
Keywords: Educational planning